Hotel Selection Decision Support System with the Simple Additive Weighting (SAW) Method - Utami, Annisaa; Usman, Muhammad Lulu Latif; Ramadhani, Ike Fitria; Syam, Siti Nur Fadilah; Fauzan, Fikrian Akmal (Forum Kerjasama Pendidikan Tinggi, 2022)
Purwokerto as the city center in southwestern Central Java which is one of the tourism places in Central Java with a fairly large number of enthusiasts. Purwokerto City has a wide selection of tourist attraction destinations that can be visited by tourists. There are not a few tourists who come from outside the city and do tours for more than one day. If you look at these conditions, a temporary stopover place is needed, namely a hotel. Purwokerto City provides so many choices of hotels spread across various locations with lodging classes, rental prices, facilities and services that are diverse. With the existence of many and different hotel facilities, of course, visitors will find it difficult to find and determine a hotel that matches the desired criteria. In addition, they will also find it difficult in finding the location of the desired hotel. The calculation results using the SAW (Simple Additive Weighting) Method found that Java Heritage Hotel got a value of 0.9, Resort and Hotel Atrium by 0.77, Surya Yudha Hotel by 0.65 and Trisno Hotel by 0.55. And get the same result between manual calculations and calculations from the system.. Based on the description above, in this study a decision support system was developed that can help tourists to determine hotels according to the wishes and needs of tourists using the SAW Method (Simple Additive Weighting)